Synthesis and Spectral Studies of Some Zn(II) Complexes with Substituted N,N-Donor Ligands Derived from Pyridine-2-carbaldehyde - Sunar, Shiva Lall; Singh, Keisham Surjit; Kundu, Sajal (Asian Journal of Chemistry, 2019)
A series of four neutral zinc complexes with substituted N,N-donor ligands viz. Ln = (E)-N-(pyridin-2-ylmethylene)anilines of composition [Zn(NO3)2(L1)] (1), [Zn(NO3)2L2] (2), [Zn(NO3)2L3] (3), [Zn(NO3)2L4] (4) were synthesized and characterized. The spectroscopic properties of the Zn(II) complexes were studied by UV-visible, fluorescence, IR and 1H NMR spectral analysis. All the zinc(II) complexes are water soluble and non-electrolyte in solution. Efforts for getting single crystals suitable for X-ray crystal structure could not be achieved. However, on the basis of spectral studies, compounds 1-4 are proposed to have octahedral geometry. The emission spectra of all the complexes show π-π* (intra-ligand) transition.